Novel Prognostic Signatures of Hepatocellular Carcinoma Based on Metabolic Pathway Phenotypes - Ye, Tingbo; Lin, Leilei; Cao, Lulu; Huang, Weiguo; Wei, Shengzhe; Shan, Yunfeng; Zhang, Zhongjing (Frontiers in Oncology, 2022)
Hepatocellular carcinoma was a disastrous cancer with aberrant metabolism. In this study, we aimed to assess the role of metabolism in the prognosis of hepatocellular carcinoma. Ten metabolism-related pathways were identified to classify the hepatocellular carcinoma into two clusters: Metabolism_H and Metabolism_L. Comparing with Metabolism_L, patients in Metabolism_H had lower survival rates with more mutated TP53 genes and more immune infiltration. Moreover, 11 differentially expressed metabolic genes-based risk score for predicting overall survival was developed by LASSO-Cox regression model in TCGA dataset, which was validated in ICGC dataset. And the immunohistochemistry staining of liver cancer patient specimens also identified that the 11 genes were associated with the prognosis of liver cancer patients. Multivariate Cox regression analyses indicated that the differentially expressed metabolic genes-based risk score was also an independent prognostic factor for overall survival. Furthermore, the risk score (AUC=0.767) outperformed other clinical variables in predicting overall survival. Therefore, the metabolism related survival-predictor model may predict overall survival excellently for HCC patients.